WASP DAN IDENTITAS AMERIKA - Eko Rujito * (Pendidikan Sosiologi FIS UNY, 2008)
There have been abundant of studies on White Anglo-Saxon Protestant and its role in shaping American culture. The assumption that America is an Anglo-Saxon Protestant nation is not entirely wrong, to certain extent, it is even indubitable. Anglo-Saxon Protestant culture and ethics have shaped America the nation it is today. This cannot be separated from the fact that the first settlers were people with Anglo-Protestant background. Through more than two hundred years of immigrations, however, when people from other parts of the globe with different cultural background and religious beliefs flooded America in huge number, this core culture did not vanish. It survived and was embraced by the majority of Americans. This paper tries to scrutinize the way the WASP identity became American identity. To do this, there are three basic ideas related to the WASP that need to be explored; the Anglo-Saxon ethnicity, Protestantism, and Anglo-conformity. In the first part it will try to investigate the significance of Anglo-Saxon ethnicity and the meaning of being an Anglo-Saxon. The second part will deal with very core of the WASP, Protestantism. In this part, this paper will answer the question on the role of Protestantism in shaping WASP identity and American identity. The last part is a discussion on the process of assimilation experienced by immigrants with non-Anglo-Saxon Protestant origins in order to be acknowledged as Americans. Keywords: WASP, American Identity, American Culture